The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/1541-4337.13156
|View full text |Cite
|
Sign up to set email alerts
|

Gluco‐oligosaccharides as potential prebiotics: Synthesis, purification, structural characterization, and evaluation of prebiotic effect

Abstract: Prebiotics have long been used to modulate the gut microbiota and improve host health. Most established prebiotics are nondigestible carbohydrates, especially short-chain oligosaccharides. Recently, gluco-oligosaccharides (GlcOS) with 2-10 glucose residues and one or more O-glycosidic linkage(s) have been found to exert prebiotic potentials (not fully established prebiotics) because of their selective fermentation by beneficial gut bacteria. However, the prebiotic effects (non-digestibility, selective fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 313 publications
0
5
0
Order By: Relevance
“…For now, the neutralization method was used for the lab-scale separation of GOS. Certainly, greener, more efficient separation methods with good scalability are needed for future large-scale production, such as nanofiltration and ion-exchange chromatography. Our laboratory has been investigating the nanofiltration separation for the purification (removal of sulfuric acid and glucose) and fractionation of oligosaccharides. The residual sulfuric acid in the permeate is proposed to be recycled and reused to improve sustainability and reduce the environmental impact of the production process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For now, the neutralization method was used for the lab-scale separation of GOS. Certainly, greener, more efficient separation methods with good scalability are needed for future large-scale production, such as nanofiltration and ion-exchange chromatography. Our laboratory has been investigating the nanofiltration separation for the purification (removal of sulfuric acid and glucose) and fractionation of oligosaccharides. The residual sulfuric acid in the permeate is proposed to be recycled and reused to improve sustainability and reduce the environmental impact of the production process.…”
Section: Resultsmentioning
confidence: 99%
“…This moderate DP range (2−4) meets the general requirement of prebiotic oligosaccharides in terms of nondigestibility and fermentability because larger oligomers would be less fermentable with lower selectivity (probably act as dietary fibers instead of prebiotics). 50 Glycosidic Linkage Analysis by HSQC NMR. The glycosidic linkages in the synthesized GOS were identified by 2D HSQC NMR in D 2 O and compared with those in the commercial β-GOS (Figure 6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 104 , 105 Prebiotic ingredients typically have a longer shelf life than probiotic ingredients, and this stability also provides convenience for storage and processing. 106 Therefore, prebiotics are gaining popularity in the field of digestive health or parenteral health.…”
Section: Treatment Of Brain Injury In Preterm Infants Mediated Throug...mentioning
confidence: 99%
“…Another challenge of the top–down method lies in the fact that the glucan oligomer concentration is lower than 5 wt % due to the limited polysaccharide solubility in most of the solvents, which inhibits its commercial application. As glucose/disaccharides have a much higher solubility in molten salt hydrates (MSHs) than polysaccharides, the bottom–up method can be carried out using concentrated glucose/disaccharides as the substrate, and it generally results in a promising glucan oligomer concentration higher than 50 wt %. , The conversion pathway of the bottom–up method involves two critical issues: (1) acid-catalyzed glycosylation among the hydroxyl groups on sugars; (2) in situ removal of the generated H 2 O from glycosylation to inhibit the rehydrolysis of the formed glucan oligomer into glucose. Recently, Zeng et al reported a simple glucan oligomer synthesis method using 76 wt % concentrated sulfuric acid as the reaction medium, achieving a promising glucan oligomer yield under mild conditions of 70 °C for 20 min .…”
Section: Introductionmentioning
confidence: 99%